Impact of Indonesia's Content Moderation Regulation on Freedom of Expression - Pingkan Audrine; Indra Setiawan (Center for Indonesian Policy Studies (CIPS), 2021)
The use of internet and digital platforms in Indonesia has been growing massively, where information exchange between users is continuous and fast-paced, especially on user-generated content (UGC) platforms such as social media, digital marketplaces, knowledge sharing, and entertainment. This highlights the need for content moderation policy to monitor UGC on the internet and prevent the spread of harmful content. Ministry of Communications and Informatics (MOCI) Regulation No. 5/2020 attempts to regulate content moderation by establishing MOCI's authority to request that private electronic system organizers (ESOs) take down prohibited content within a restricted time period. While weak content moderation comes with a risk of harmful material, excessive content moderation may turn into excessive censorship that could violate individual freedom of expression. To address issues in MOCI Regulation No. 5/2020, this policy paper proposes several recommendations for Indonesia's content moderation policy.
Keywords: 330; internet; digital platforms; Indonesia content moderation; content moderation; user-generated content; indonesia social media; MOCI; ministry of communication and informatics; digital content; social modia content; indonesia social media content; internet sharing; sharing content through internet; MOCI regulation no 5/2020; electronic system organizer; indonesia electronic system organizer; indonesia eso; indonesia instagram; indonesia twitter; indonesia whatsapp; indonesia content regulation; indonesia social media regulation; social media regulation; freedom of expression